Crystal-field level inversion in lightly Mn-doped Sr3Ru2O7 - Hossain, Suman; Haverkort, Maurits W. (Arxiv, 2008)
Sr3(Ru1-xMnx)2O7, in which 4d-Ru is substituted by the more localized 3d-Mn, is studied by x-ray dichroism and spin-resolved density functional theory. We find that Mn impurities do not exhibit the same 4+ valence of Ru, but act as 3+ acceptors; the extra eg electron occupies the in-plane 3dx2-y2 orbital instead of the expected out-of-plane 3d3z2-r2. We propose that the 3d-4d interplay, via the ligand oxygen orbitals, is responsible for this crystal-field level inversion and the material's transition to an antiferromagnetic, possibly orbitally-ordered, low-temperature state.